Re Investigation into the Relation Between Financial Development and Investments in India - Menon, Priyanka; Kumar, Lakshmi (Asian Journal of Empirical Research, 2018)
This study aims at investigating the relation between financial development, trade openness and investment activities in India. The study makes use of Autoregressive Distributed Lag (ARDL) bounds testing approach. The long run relationship between the variables is established for the period ranging from 1961-2015. Time series analysis is incorporated for understanding the relation between investment and financial development. We created a composite term for measuring financial development. The results suggest that financial development has positive impact on investment. Therefore, we could say that investment activities in India are financial development driven. The speed of adjustment is 43.5%. The error correction term (ECT) is negative which is appropriate. In contrast, the findings also reveal that the trade openness has a negative impact on investment. The model used in our study gives desirable results which imply that for an improved productivity of a nation, investments have to be induced and this would be enhanced by a sound financial system.